The Center for Medicare and Medicaid Innovation: The Case for Reform - Doug Badger MDiv (SAGE Publishing, 2022)
Congress created the Center for Medicare and Medicaid Innovation and vested it with extraordinary authority. CMMI tests the hypothesis that policy experts and civil servants, insulated from the vicissitudes of the political process and accorded quasi-legislative authority, could conceive and implement transformative health care financing policy innovations that Congress could neither devise nor enact. Twelve years after its founding, CMMI has disappointed these expectations. Only 6 of the more than 50 models it has tested have met de minimis measures of success (no increase in federal spending or diminution of quality). The incremental savings associated with these 6 models have been more than offset by a string of failed concepts. More significantly, none of the demonstration projects deemed successful has resulted in scalable reforms that meet statutory criteria of reducing health care spending or enhancing its quality. CMMI has increased federal spending without producing meaningful reforms of federal health care entitlement programs. This paper will review CMMI's statutory authorities and track record and show how faulty fiscal assumptions made by the Congressional Budget Office can impede congressional efforts to reform CMMI. It will also discuss how the law has inverted the relationship between the legislative and executive branches, requiring an Act of Congress to prevent CMMI from effectively amending federal statutes. It recommends that CBO modify its assumptions to reflect that CMMI has not produced federal savings. It also recommends that Congress curtail CMMI's powers and shoulder the obligation of reforming federal entitlement programs.